REDUCTIVE CONSTRUCT OF RELIGION IN THE FRAME OF SECTARIAN THEOLOGICAL INTERPRETATION - Badarussyamsi Badarussyamsi; Ermawati Ermawati (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2021)
This article elucidates contradictory religious arguments. Religion substantively carries messages of salvation and guidance of truth from God. But when it is practiced by humans, substantive religious messages were reduced and replaced with contradictory religious expressions that eradicated the substantive messages of religion itself. Conflict and violence in the name of religion is a real phenomenon that the substantive religious teachings lost its essential message of religion. An important question to be answered in this article is how does the process of religious reduction occur if it is reviewed from the character of theological interpretation produced by theologians? A literature study of this article about the tension, conflict, and violence in the name of religion shows that the reduction of the face of religion is due to the product of sectarian, fanatical, and untolerant. These findings strengthen previous studies about the influence of theological patterns towards religious attitudes of their adherents.